Regulation of alfalfa growth, water and nitrogen utilization and distribution in arid region of Northwest China by optimizing irrigation method - Ma, Hongxiu; Jiang, Peng; Zhang, Xiaojuan; Liu, Ruliang; Sun, Quan; Wang, Lei (Frontiers in Plant Science, 2025)
The water and nitrogen use efficiency of alfalfa is very low in the arid region of Northwest China currently. In this field experiments in 2022 and 2023, the effects of traditional flood irrigation (FI-12, 1200 mm; FI-8, 880 mm), sprinkler irrigation (SI-8, 880 mm; SI-5, 520 mm), and subsurface drip irrigation (DI-5, 520 mm; DI-8, 880 mm)) on alfalfa yield, water use efficiency (WUE), and nitrogen use efficiency (NUE) were studied. The results showed that the DI and SI treatments, especially DI-5, increased alfalfa seed yield by increasing the number of inflorescences and pods compared with the FI treatments. The DI and SI treatments, especially DI, reduced water loss during the first two crops in each growing season compared with the FI treatments, improving the WUE. The DI treatments had the lowest root/shoot ratio (R/S), which facilitated the distribution of photosynthetic products to the reproductive organs and inhibited the overgrowth of the root system. The small R/S in the late growth stage of the DI-5 treatment also helped to achieve high WUE. Besides, the DI treatments also had the largest root length density, which promoted the uptake and utilization of water and nitrogen by alfalfa. The DI treatments increased the nitrogen accumulation of plants, and reduced the soil nitrate (NO3−-N) leaching and NH3 volatilization at maturity stage compared with the SI and FI treatments, improving the NUE. In summary, the subsurface drip fertigation, especially DI-5, coordinated the vegetative and reproductive growth, and reduced the water loss, nitrate leaching, and NH3 volatilization, improving the seed yield, WUE, and NUE of alfalfa. This study will advance understanding of the mechanism of subsurface drip irrigation regulating alfalfa root growth and water and nitrogen use, and provide a scientific basis for the application of subsurface drip fertigation in arid and semi-arid areas.